Participatory design of street vendor tents at PKL Wahidin, Yogyakarta City - Tutun Seliari; Imelda Irmawati Damanik; Yohanes Satyayoga Raniasta (University of Merdeka Malang, 2021)
The existence of street vendors (in Indonesian called Pedagang Kaki Lima/PKL), who are often shabby and disturb the visual image of the city, has become an issue raised in this community service program. This service program assists PKL Communities along Wahidin Sudirohusodo Street Yogyakarta (in front of the Duta Wacana Christian University Campus). The PKL Wahidin community has the intention to improve itself to organize street vendors that involve relevant stakeholders (according to the Yogyakarta City ‘gandeng-gendong’ program) it is hoped that it can become an identity for an image of a city in Yogyakarta. The process of designing street vendors tents using participatory design methods, community-based design with stages in the form of surveys, observations, interviews, Focus Group Discussion (FGD), and making tent design mockups. The participatory design method chosen was expected to make the community have a ‘sense of belonging’ to the arrangement of street vendors along Wahidin Street so that sustainability would be created. This tent design can later be moved (movable) and following user needs and because the location of the design sidewalks remains environmentally friendly to pedestrians.